Undescribed sesquiterpene coumarins from the aerial parts of Ferula sinkiangensis and their anti-inflammatory activities in lipopolysaccharide-stimulated RAW 264.7 macrophages. (June 2023) - Wang, Junchi; Huo, Xiaoshuang; Wang, Huaxiang; Dong, Aijun; Zheng, Qi; Si, Jianyong
Abstract: Eight undescribed sesquiterpene coumarins (1 –8 ) and twenty known ones (9 –28 ), were isolated from the aerial parts of Ferula sinkiangensis K. M. Shen. Their structures were elucidated based on the comprehensive analysis of UV, IR, HRESIMS, 1D, and 2D NMR data. The absolute configuration of 1 was determined by single crystal X-Ray diffraction, while the absolute configurations of 2 –8 were determined by comparisons of experimental and calculated electrostatic circular dichroism spectra. Compound 2 is the first hydroperoxy sesquiterpene coumarin from the genus Ferula, while compound 8 has an unusual 5′, 8′-peroxo bridge. Griess reaction results indicated compound 18 significantly decreased nitric oxide production of the lipopolysaccharide-stimulated RAW 264.7 macrophages with an IC50 value of 2.3 μM, and ELISA results revealed that compound 18 effectively inhibited tumor necrosis factor- α, interleukin (IL)-1 β, and IL-6 expressions. Graphical abstract: Eight undescribed sesquiterpene coumarins and twenty known ones were isolated from the aerial parts of Ferula sinkiangensis . Eighteen compounds displayed inhibitory effects on NO production with IC50 values ranging from 2.3 to 46.7 μM. Image 1 Highlights: Eight undescribed coumarin derivatives were isolated from Ferula sinkiangensis. Absolute configurations were elucidated by single crystal X-Ray and ECD simulation. Compound 2 is the first hydroperoxyl sesquiterpene coumarin from the genus Ferula. Compound 18 significantly decreased NO production with an IC50 value of 2.3 μM.